Anthropometric study of UiTM students (male) / Mohammad Fitri Shuib - Shuib, Mohammad Fitri (2010)
Anthropometry is defined as a measurement of the human body and its biomechanical characteristics. The project is carried out in order to establish the anthropometric data of male UiTM students. The development of this data will benefit the industrial designers and help university students to carry out any project that related to this data, especially in the biomechanical-related field. The data is collected among 50 male respondents, aged vary from 20 to 24 years old. 24 anthropometric dimensions were obtained from each of the respondents using a traditional anthropometer. The measuring process is carried out according to the Malaysian Standard 2003; MS ISO 7250:2003- Basic Measurements for Technological Design. All the landmarks, measuring procedures and postures are closely referred. It is often assumed that the anthropometric dimensions of the human body in a population are normally distributed, hence the mean, 5th and 95th percentile value are critical for the application of the anthropometric data. A proper definition for each of the anthropometric dimensions is included. The study also compare the significant differences in anthropometric dimension between respondents originated from 5 different regions of Malaysia; Northern Peninsular, Eastern Coast Peninsular, Central Peninsular, Southern Peninsular Malaysia and East Malaysia (Sabah & Sarawak).